2017
DOI: 10.1021/acs.est.7b02157
|View full text |Cite
|
Sign up to set email alerts
|

Dissolved CO2Increases Breakthrough Porosity in Natural Porous Materials

Abstract: When reactive fluids flow through a dissolving porous medium, conductive channels form, leading to fluid breakthrough. This phenomenon is caused by the reactive infiltration instability and is important in geologic carbon storage where the dissolution of CO in flowing water increases fluid acidity. Using numerical simulations with high resolution digital models of North Sea chalk, we show that the breakthrough porosity is an important indicator of dissolution pattern. Dissolution patterns reflect the balance b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 88 publications
(207 reference statements)
0
14
0
Order By: Relevance
“…We used a conventional CFD approach (finite volume method to solve the Stokes equation on binarised tomogram [ 48 ]) to show that the influence is rock type specific and is predominately reflected in the interconnectivity of pore spaces that require discretisation. We have also applied the reactor network model on tomographic data at three different resolutions [ 34 ]. The results suggested that both the effect of the voxel size and that of the initial microstructure are secondary compared to the apparent solubility of the solid in the flowing fluid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used a conventional CFD approach (finite volume method to solve the Stokes equation on binarised tomogram [ 48 ]) to show that the influence is rock type specific and is predominately reflected in the interconnectivity of pore spaces that require discretisation. We have also applied the reactor network model on tomographic data at three different resolutions [ 34 ]. The results suggested that both the effect of the voxel size and that of the initial microstructure are secondary compared to the apparent solubility of the solid in the flowing fluid.…”
Section: Discussionmentioning
confidence: 99%
“…We adopted the model framework of Yang et al . [ 32 34 , 37 ]. The mathematical scheme is designed to treat the assemblage of greyscale voxels as a network of ideal chemical reactors.…”
Section: Methodsmentioning
confidence: 99%
“…In geologic carbon sequestration (DePaolo & Cole, ; Fitts & Peters, ; Zhang & Liu, ) and in acid stimulation in oil fields (Hoefner & Fogler, ), injecting erosive fluids generates complex flow pathways. Managing the development of such networks, that is, controlling the rate of network expansion while regulating the size distribution of the growing channels, is essential for properly distributing CO 2 into porous formations (Abdoulghafour et al, ; Deng et al, , ; Ellis et al, ; Luquot & Gouze, ; Noiriel, ; Yang et al, ) and for effectively recovering hydrocarbons from reservoirs (Fredd & Fogler, ; Hoefner & Fogler, ; Rege & Fogler, ).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we define cumulative surface (CS) as the amount of surface area to which fluid has access within the residence time. This concept was first coined to quantify the reactive subvolume of porous media (Yang et al, ; Yang, Bruns, Rogowska, et al, ). Here we further argue that CS, by integrating the effects of residence time, reaction rate, and initial pore heterogeneity into one quantity, also helps identify the trajectory of localized pore development.…”
Section: Introductionmentioning
confidence: 99%
“…This disequilibrium is the driving force for geochemical reactions which modify rock properties, such as mineral dissolution and precipitation. This modification, in turn, provides feedback on the migration of fluid that carries the reactants and products for these reactions (Yang et al, 2016a). This coupled evolution of flow field and microstructure through chemistry is far from being understood because of the difficulties in direct experimental observation (Noiriel, 2015) and in numerically handling mathematical models based on free boundary problems of partial differential equations (Chadam et al, 1986;Ortoleva et al, 1987;Szymczak and Ladd, 2012;Yang et al, 2016b).…”
Section: Introductionmentioning
confidence: 99%